Covid-19 Vaccination Rights and Obligations in Indonesia from a Legal Perspective - Gunawan Nachrawi; Ryan Hidayat; Marjan Miharja; Rahmat Dwi Putranto; Yastuty Handalya (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Indonesia declares a state of emergency due to Pandemic Covid-19. Indonesia declared a state of health emergency in 2020 via Presidential Decree No. 11. Numerous measures have been undertaken to mitigate the consequences of the Covid-19 epidemic. Vaccination is one of the government's attempts. However, in the prosocity of vaccination-related benefits and drawbacks. Numerous individuals refused to be vaccinated. This research is legal in nature and is doctrinal in nature. It employs a conceptual method and a legislative approach (statue approach) to the handling of Pandemic Covid-19 in Indonesia. The study's findings show that immunizations are provided free of charge, which, while initially a right of each citizen, may become a responsibility in light of Indonesia's present state of health emergency. This is possible because an individual who is not vaccinated has the ability to transfer the disease to others.